Gold-Catalyzed Complementary Nitroalkyne Internal Redox Process: A DFT Study - Vipin Raj, K.; Dhote, Pawan S.; Vanka, Kumar; Ramana, Chepuri V. (Frontiers in Chemistry, 2021)
Gold-catalysis, in this century, is one of the most emerging and promising new areas of research in organic synthesis. During the last two decades, a wide range of distinct synthetic methodologies have been unveiled employing homogeneous gold catalysis and aptly applied in the synthesis of numerous natural products and biologically active molecules. Among these, the reactions involving alpha-oxo gold carbene/alpha-imino gold carbene intermediates are of contemporary interest, in view of their synthetic potential and also due to the need to understand the bonding involved in these complexes. In this manuscript, we document the theoretical investigations on the regio-selectivity dependence of substitution on the gold-catalyzed cycloisomerization of o-nitroarylalkyne derivatives. We have also studied the relative stabilities of alpha-oxo gold carbene intermediates.